A Five-MicroRNA Signature Predicts the Prognosis in Nasopharyngeal Carcinoma - Wu, Shixiong; Zhang, Cen; Xie, Jing; Li, Shuang; Huang, Shuo (Frontiers in Oncology, 2021)
Background: There is no effective prognostic signature that could predict the prognosis and the chemotherapy response of nasopharyngeal carcinoma (NPC). Methods: We constructed a prognostic signature based on 5-microRNA using random forest and Least Absolute Shrinkage And Selection Operator (LASSO) algorithm on the GSE32960 cohort (N = 213). We verified its prognostic value using three independent external validation cohort (GSE36682, N = 62; GSE70970, N = 246; TCGA-HNSC, N = 523). Through principal component analysis, receiver operating characteristic curve analysis and C-index calculation, we confirmed the predictive accuracy of this prognostic signature. Results: We calculated a risk score based on the LASSO algorithm, and divided the patients into the high- and low-risk group according to the calculated optimal cut-off value. The patients in the high-risk group tended to have a worse prognosis outcome and chemotherapy response. The time-dependent ROC curve showed that the 1-year overall survival rate of 5-microRNA signature had an AUC of more than 0.83. Functional annotation analysis of 5-microRNA signature showed that patients in the high-risk group were usually accompanied by activation of DNA repair and MYC-targets pathways, while patients in the low-risk group had higher immune-related pathway signals. Conclusions: We constructed a 5-microRNA prognostic signature, which could accurately predict the prognosis and chemotherapy response of nasopharyngeal carcinoma, and constructed a nomogram that could conveniently predict the overall survival of patients.